1993
DOI: 10.1007/bf00381344
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of S-hydroxyguanine in peripheral blood cells: An application for asbestosis patients

Abstract: The quantitative analysis of 8-hydroxy-2'-deoxyguanosine (oh8dG) in human peripheral blood cells was carried out to find integrated biomarkers for estimating cancer risk. The change of the oh8dG levels over time in two healthy volunteers was measured to evaluate a intraindividual variance and each individual value was confirmed to be almost constant when they maintained usual life style. We applied this measurement to asbestosis patients who had worked in dockyard for 19-42 years. The oh8dG were detected in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Our results are in good agreement with the data of Schins et al (1995), who reported identical 8-OHdG/ dG ratios in lymphocytes of miners with and without coal workers' pneumoconiosis. A similar study by Hanaoka et al (1993) on 8-OHdG in peripheral blood cells yielded equal levels of 8-OHdG in asbestosis patients and in a control group without asbestos exposure. In contrast, Takahashi et al (1997) reported a positive gradient of leukocytic 8-OHdG in relation to increasing grades of asbestosis, and the 8-OHdG levels were found to correlate with the cumulative asbestos-exposure indices, suggesting that chronic exposure to asbestos per se induces oxidative DNA damage.…”
Section: Resultssupporting
confidence: 51%
“…Our results are in good agreement with the data of Schins et al (1995), who reported identical 8-OHdG/ dG ratios in lymphocytes of miners with and without coal workers' pneumoconiosis. A similar study by Hanaoka et al (1993) on 8-OHdG in peripheral blood cells yielded equal levels of 8-OHdG in asbestosis patients and in a control group without asbestos exposure. In contrast, Takahashi et al (1997) reported a positive gradient of leukocytic 8-OHdG in relation to increasing grades of asbestosis, and the 8-OHdG levels were found to correlate with the cumulative asbestos-exposure indices, suggesting that chronic exposure to asbestos per se induces oxidative DNA damage.…”
Section: Resultssupporting
confidence: 51%
“…Therefore, the measurement of 8-OH-dG is considered to be useful for the assessment of occupational carcinogenic risk. Indeed, many studies have investigated the relationships between work-related hazardous substances and oxidative DNA injury (Kasai and Nishimura 1984b;Hanaoka et al 1993;Yamano et al 1995;Tagesson et al 1996;MurataKamiya et al 1997;Takahashi et al 1997). For example, we reported that the production of 8-OH-dG in calf thymus DNA was induced by asbestos in the presence of hydrogen peroxide (Kasai and Nishimura 1984b).…”
Section: Introductionmentioning
confidence: 82%
“…Tagesson et al (1993) found a signiWcantly higher urinary excretion of 8-OHdG in 30 asbestos exposed workers as compared to 41 controls. Hanaoka et al (1993) measured 8-OHdG in peripheral blood cells of asbestosis patients, observing no signiWcant diVerence in the level of 8-OHdG between patients and controls without asbestos exposure. Therefore, the authors concluded that 8-OHdG is not a sensitive marker for past asbestos exposure at low levels.…”
Section: Asbestosmentioning
confidence: 99%
“…Leukocytes HPLC-EC 1.00 § 0.17/10 5 dG (asbestos patients, n = 7) 1.03 § 0.20/10 5 dG (controls, n = 6) Hanaoka et al (1993) 54.9 § 4.3 55.3 § 4.5 54.3 § 4.5…”
Section: Smokingmentioning
confidence: 99%